2015
DOI: 10.1080/2159256x.2015.1086502
|View full text |Cite
|
Sign up to set email alerts
|

The peculiarities of piRNA expression upon heat shock exposure inDrosophila melanogaster

Abstract: Different types of stress including heat shock may induce genomic instability, due to the derepression and amplification of mobile elements (MEs). It remains unclear, however, whether piRNA-machinery regulating ME expression functions normally under stressful conditions. The aim of this study was to explore the features of piRNA expression after heat shock (HS) exposure in Drosophila melanogaster. We also evaluated functioning of piRNAmachinery in the absence of major stress protein Hsp70 in this species. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
(79 reference statements)
4
10
0
Order By: Relevance
“…Pre-processing and mapping of small RNA libraries to the dm3 Drosophila genome assembly was performed as previously described [27]. The number of reads mapped to the miRNAs was counted, using the B ed T ools toolkit (v. 2.22) and miRBase (r.19) annotation [53].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-processing and mapping of small RNA libraries to the dm3 Drosophila genome assembly was performed as previously described [27]. The number of reads mapped to the miRNAs was counted, using the B ed T ools toolkit (v. 2.22) and miRBase (r.19) annotation [53].…”
Section: Methodsmentioning
confidence: 99%
“…We performed this analysis using a D. melanogaster ‘hsp70 − strain’ that lacks all hsp70 genes [26]. Recently, using the same model system, we analysed the deep-sequencing data of piRNA expression after HS treatment and demonstrated that HS results in strain-specific expression modulation of certain double-stranded piRNA clusters [27]. …”
Section: Introductionmentioning
confidence: 99%
“…tuberculosis infection have been suggested to be a possible bacterial evasion mechanism (42, 43), which might explain the different piRNA signatures identified here. Another plausible explanation is that piRNA are simply dysregulated upon cellular stress (44). However, very little is known about the full spectrum of piRNA functions beyond the original concept that they interfere with replication of endogenous retroviruses in germ line cells.…”
Section: Discussionmentioning
confidence: 99%
“…2001). A previous study proposed the possible involvement of Hsp70 in the biogenesis of piRNA in Drosophila following severe heat-shock conditions, but could not conclusively determine the details of this regulatory process (Funikov et al 2015). This, in combination with our findings, suggest that piRNAs may be involved in the heat-stress induced response mediated by increased Hsp70 levels for normal development.…”
Section: Discussionmentioning
confidence: 99%